O modelo anisotrópico Ginzburg-Landau e a determinação de campos magnéticos dispersos em nanoestruturas híbridas supercondutoras-ferromagnéticas - Paschoa, Anderson dos Santos (2020)
In this doctorate thesis, the Ginzburg-Landau anisotropic model was experimentally tested. The physical parameter ∆ = || −⊥ was defined, where || and ⊥ represent the superconducting critical temperatures (), determined in the magnetic field settings applied parallel (B||) and perpendicular (B⟘) to the sample plane, respectively. Using the Magnetron Sputtering technique (operating in the confocal geometric configuration), superconducting films Nb(20=100), SC/FM superconducting-ferromagnetic hybrid heterostructures [Nb(20-100)/Cu(5)/Co(40) and Nb(20-100)/Cu(5)/Py(2)] and said superconducting spin valves SC/FM1/FM2 VSS [Nb(20- 100)/Cu(5)/Py(2)/Cu(5)/Co(40)] were prepared, where the values in parentheses are in nanometers. The anisotropic behavior of Tc and the VSS effect under the application of the magnetic field were systematically investigated. With magnetoresistance measurements in the magnetic field configurations used (B|| and B⟘), it was possible to obtain the experimental behavior of ∆ for each hybrid SC/FM system and applying the anisotropic model of Ginzburg-Landau, the dispersed magnetic field values of the FM layers were calculated in the condition of a null magnetic field, that is, the stray field of the Co, Py e Py/Co (in the VSS system) layers were determined in zero applied field (B = 0 T) as being repectively (- 8,5 ± 0,1) mT, (31,0 ± 0,3) mT e (38,0 ± 0,4) mT, while a rate of change between the stray field and applied field ( / ) was of (- 0,22 ± 0,02), (- 0,17 ± 0,02) and (- 0,26 ± 0,02), respectively. With angular dependence measurements of the magnetoresistance, ∆ (, ) curves for pure Nb films and Nb/FM hybrids were obtained, and large effect values of the superconducting spin valve (EVSS) between 60 and 300 mK were measured. Instead of simply using the possibility of transitioning Cooper pairs from singlet to triplet state, the EVSS results were explained considering the effective dispersed field derived from changes in the magnetic domains of the ferromagnetic layers caused by the external magnetic field. The results bring contributions to clarify the proximity effect and the magnetostatic effect; issues that still need to be well understood for technological applications of superconducting spin valves.